EXAMINING THE EFFECT OF INTERNET ADDICTION ON THE ACADEMIC PERFORMANCE OF UNDERGRADUATE STUDENTS - Tasleem Kanwal; Shabana Samreen; Uzma Munawar (International Journal of Contemporary Issues in Social Sciences, 2024)
The purpose of this study was to look at the connection between undergraduate students’ academic achievement and Internet addiction. The study also looked at how students’ internet addiction varied according to their gender. One hundred undergraduates from universities made up the sample. Descriptive statistics, t-tests, ANOVA, and basic linear regression analysis were used to gather and examine their answers to the "Internet Addiction Scale" and their GPA from the prior semester. The findings showed a strong inverse relationship between undergraduate university students’ academic achievement and internet addiction. The findings also showed that there are gender disparities in internet addiction, with male students showing higher levels of addiction than female students. A number of recommendations were made for future study and practical applications in light of these findings.